Pemanfaatan Limbah Rumah Tangga Untuk Pembuatan Pupuk Organik Cair di Desa Panjunan Sukodono Sidoarjo - Haidar Fari Aditya; Noni Rahmadhini; Ramadhani Mahendra Kusuma; Fitri Wijayanti; Safira Rizka Lestari (Gapenas Publisher, 2022)
The volume of waste or residual materials arising from human fulfillment increases annually in line with the growth of the human population. The potential of household units to manage organic waste has the potential to minimize food waste and other forms of organic waste. Utilizing organic waste as a raw material for composting is an option for handling organic waste from households. This community service project aims to demonstrate to the community how to make liquid organic fertilizer and raise public awareness of the advantages of managing household waste. Training combined with direct demonstrations via interactive learning covering household waste sorting and composting techniques was performed. This event was attended by 25 community household representatives from Panjunan Village, Sukodono, Sidoarjo. The demonstration method that was used was thought to be effective because the community was interested and came up with new ways to use empty land as a follow-up after creating liquid organic fertilizer on its own